High specificity and sensitivity of Zika EDIII-based ELISA diagnosis highlighted by a large human reference panel. - Jessica Denis; Sarah Attoumani; Patrick Gravier; Bernard Tenebray; Annabelle Garnier; Sébastien Briolant; Franck de Laval; Véronique Chastres; Gilda Grard; Isabelle Leparc-Goffart; Bruno Coutard; Cyril Badaut (Public Library of Science (PLoS), 2019)
Background Zika virus (ZIKV) and Dengue virus (DENV) are often co-endemic. The high protein-sequence homology of flaviviruses renders IgG induced by and directed against them highly cross-reactive against their antigen(s), as observed on a large set of sera, leading to poorly reliable sero-diagnosis. Methods We selected Domain III of the ZIKV Envelope (ZEDIII) sequence, which is virus specific. This recombinant domain was expressed and purified for the specific detection of ZEDIII-induced IgG by ELISA from ZIKV-RT-PCR-positive, ZIKV-IgM-positive, flavivirus-positive but ZIKV-negative, or flavivirus-negative sera. We also assessed the reactivity of ZEDIII-specific human antibodies against EDIII of DENV serotype 4 (D4EDIII) as a specific control. Sera from ZEDIII-immunized mice were also tested. Results Cross-reactivity of IgG from 5,600 sera against total inactivated DENV or ZIKV was high (71.0% [69.1; 72.2]), whereas the specificity and sensitivity calculated using a representative cohort (242 sera) reached 90% [84.0; 95.8] and 92% [84.5; 99.5], respectively, using a ZEDIII-based ELISA. Moreover, purified human IgG against D2EDIII or D4EDIII did not bind to ZEDIII and we observed no D4EDIII reactivity with ZIKV-induced mouse polyclonal IgGs. Conclusions We developed a ZEDIII-based ELISA that can discriminate between past or current DENV and ZIKV infections, allowing the detection of a serological scar from other flaviviruses. This could be used to confirm exposure of pregnant women or to follow the spread of an endemic disease.